Animal Models for Investigating Osseointegration: An Overview of Implant Research over the Last Three Decades - Antonio Scarano; Ahmad G. A. Khater; Sergio Alexandre Gehrke; Francesco Inchingolo; Sergio Rexhep Tari (Journal of Functional Biomaterials, 2024)
Dental implants and bone augmentation are among dentistry’s most prevalent surgical treatments; hence, many dental implant surfaces and bone grafts have been researched to improve bone response. Such new materials were radiologically, histologically, and histomorphometrically evaluated on animals before being used on humans. As a result, several studies used animals to evaluate novel implant technologies, biocompatibility, surgical techniques, and osseointegration strategies, as preclinical research on animal models is essential to evaluate bioactive principles (on cells, compounds, and implants) that can act through multiple mechanisms and to predict animal behavior, which is difficult to predict from in vitro studies alone. In this study, we critically reviewed all research on different animal models investigating the osseointegration degree of new implant surfaces, reporting different species used in the osseointegration research over the last 30 years. Moreover, this is the first study to summarize reviews on the main animal models used in the translational research of osseointegration, including the advantages and limitations of each model and determining the ideal location for investigating osseointegration in small and large animal models. Overall, each model has advantages and disadvantages; hence, animal selection should be based on the cost of acquisition, animal care, acceptability to society, availability, tolerance to captivity, and housing convenience. Among small animal models, rabbits are an ideal model for biological observations around implants, and it is worth noting that osseointegration was discovered in the rabbit model and successfully applied to humans.